Pemberdayaan Perempuan dalam Manajemen Kota: Mendukung Partisipasi Perempuan dalam Pengambilan Keputusan Perkotaan - Kusuma Fadhillah, Nayma; Nicole L Tobing, Angeliq; Aisyah Diva Maha, Ratu; Anom Rahmadana, Yeto (Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
The main problem that needs to be researched is gender inequality in city management which hinders women's participation in urban decision making. This research aims to analyze the impact of gender inequality on women's participation in urban decision making in Indonesia. The research method used is qualitative, with a focus on identifying structural, normative and gender stereotype barriers that limit women's access to key policy positions. The research findings highlight the need for women's empowerment through leadership training, implementation of women's representation quotas, and gender awareness campaigns as strategies to address inequality. The results of this research confirm that women's empowerment not only acts as a strategic solution, but also creates a solid foundation for increasing inclusiveness in city management. Therefore, concrete steps such as training and women's representation quotas can work together to overcome these obstacles, paving the way for greater women's participation in urban decision-making. Therefore, concrete steps such as training and women's representation quotas can work together to overcome these obstacles, paving the way for greater women's participation in urban decision-making. This research makes a significant contribution to the development of policy science by offering an in-depth understanding of the complexity of gender inequality and providing insight into strategic solutions that can be implemented in the context of city management in Indonesia.